KOMUNIKASI DALAM PENDEKATAN ISLAM (Telaah Teoretis tentang Kajian Komunikasi dengan Allah melalui Shalat dan Membaca Al-Qur’an) - ZIKRI FACHRUL NURHADI (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2015)
Al-Qur’an as Words of God actually is the channel of communication between God and man. Based on the system of revelation from God to Gabriel, from Gabriel to Muhammad, from Muhammad to man, it shows the possibility of opening abstract or non verbal communication between God and man. When one reads Al-Qur’an actually he/she communicates with God. When one observes shalat or haji or says a word of Qur’an, he/she behaves like Muhammad when he recieved or communicated with God and Gabriel. In terms of Wahyu there were two dimensions: aural dan oral. People had both like Muhammad SAW, if they read the Qur’an. So, reading the Qur'an and observing prayers are part of communicating with the Creator.